Sosialisasi Konsep Lahan Pertanian Pangan Berkelanjutan Di Kecamatan Batang Tuaka, Kabupaten Indragiri Hilir - Mulono Apriyanto; KMS. Novyar Satriawan Fikri; Ali Azhar (Yayasan Pendidikan Penelitian Pengabdian Algero, 2021)
Availability of land for agriculture is an absolute requirement to achieve self-reliance, security and food sovereignty. However, Indonesian farmland tends to decline due to land conversion. Therefore, determining sustainable food farmland and regulating the conversion of food farmland is one of the most strategic policies to achieve food security. The Spatial Plan of the Province of Riau in the Spatial Pattern Plan section states that one of the areas focused on wetland agriculture (rice) is Indragiri Hilir Regency. However, the high conversion of agricultural land threatens the survival of Sustainable Food Agricultural Land. Since the LP2B policy is very dependent on the willingness of the farmers who own the fields, it is considered necessary to socialize the concept of this LP2B policy among farmers so that they can support government policy in achieving food sovereignty. The results of the analysis show that Batang Tuaka sub-district has the potential to be used as Sustainable Food Agricultural Land (LP2B), but unfortunately this is not supported by farmers' knowledge and understanding of the LP2B concept, so the conversion of farmland is becoming more common and can threaten the realization of food security in Indragiri Hilir Regency.